Film Aceh dalam Perspektif Etika Komunikasi Islam - Al Zuhri; Heri Rahmat Syahputra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The goal of this study was to look at the use of ethics in Aceh's cinema, namely, as an area of Islamic law. Qualitative content analysis with an explanatory approach was employed as the strategy. Meanwhile, documentation were employed to obtain data. The study's focus is on audiovisual items of Aceh movie video compact disc,